Individualized Technique Feedback for Instant Technique Improvements and Knee Abduction Moment Reductions – A New Approach for ‘Sidestepping’ ACL Injuries? - Kevin Bill; Patrick Mai; Lasse Mausehund; Sigurd Solbakken; Tron Krosshaug; Uwe G. Kersting (International Journal of Sports Physical Therapy)
# Background